Early childhood centre children in an interactive science gallery : a thesis presented in partial fulfilment of the requirements for the degree of Master of Education at Massey University - Ellis, Jill A (Massey University, 1998)
The Science Centre & Manawatu Museum (TSC&MM) was established with monetary support from the Palmerston North City Council and Lotteries Board. The science gallery, Kids Own (KO), is designed especially for children 0 to 8 years of age and usually contains fourteen exhibits which young children and their accompanying adults are invited to explore. This research investigates use of the Kids Own gallery by people in the Early Childhood Education (ECE) sector. The data were gathered by a questionnaire administered to all Early Childhood Centre (ECC) staff in the catchment area of The Science Centre & Manawatu Museum, and by audio-recording, observing, and later interviewing children from 3 Early Childhood Centres who visited the Kids Own gallery. The findings of phase one of this study suggest that Early Childhood Centre staff are composing groups of children and adults from their centres to visit the Kids Own gallery. Interaction among peers is relied upon for children to learn about phenomena in the world and develop their concepts of how the world works. Phase two of this study was conducted to record the interactions of early childhood staff, adults, and peers with the exhibits, and with each other while visiting an interactive science centre gallery. Major findings include: That The Science Centre & Manawatu Museum is perceived by most early childhood educators to be meeting the needs of young children and staff from Early Childhood Centres; That Early Childhood Centre staff have taken groups of young children to the Kids Own gallery because they perceive it enables them to meet all the principles of the current early childhood curriculum; That the peers and ECC staff in the gallery scaffolded children's interactions with exhibits; That girls showed a preference for sensory exhibits and activities with child peers, while boys engaged in interactions with adults, primarily at physical science exhibits; That there are issues regarding the creation, placement, publicity, and appropriateness of exhibits designed for young children.
Keywords: Science study and teaching; Science museums, New Zealand; Science Centre & Manawatu Museum; Preschool science